2011
DOI: 10.1371/journal.pone.0028087
|View full text |Cite
|
Sign up to set email alerts
|

Magnetoencephalography Study of Right Parietal Lobe Dysfunction of the Evoked Mirror Neuron System in Antipsychotic-Free Schizophrenia

Abstract: IntroductionPatients with schizophrenia commonly exhibit deficits of non-verbal communication in social contexts, which may be related to cognitive dysfunction that impairs recognition of biological motion. Although perception of biological motion is known to be mediated by the mirror neuron system, there have been few empirical studies of this system in patients with schizophrenia.MethodsUsing magnetoencephalography, we examined whether antipsychotic-free schizophrenia patients displayed mirror neuron system … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
34
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 46 publications
(46 reference statements)
3
34
0
Order By: Relevance
“…In conclusion, our study supports previous evidence of poorer mnES during action observation in schizophrenia [21,22,23,24]. Moreover, it goes further by showing that emotional cues might allow patients to recover mnES, at least in part.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…In conclusion, our study supports previous evidence of poorer mnES during action observation in schizophrenia [21,22,23,24]. Moreover, it goes further by showing that emotional cues might allow patients to recover mnES, at least in part.…”
Section: Discussionsupporting
confidence: 91%
“…Evidence of poorer mnES comes from transcranial magnetic stimulation studies [21,22] and from magneto-encephalography studies [23,24]. For example, deficient motor facilitation during action observation relative to the resting state was detected in antipsychotic-naive SCZ patients as compared with medicated SCZ patients and healthy comparison subjects [22].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In schizophrenia and related disorders, a dysfunctional mirror neuron system (MNS) in comparison to healthy controls has been observed by various authors (Mitra et al, 2014a;Kato et al, 2011;Rizzolatti et al, 1998). Recent work to explore the temporal evolution of MNS function has revealed that in patients with schizophrenia, this dysfunction did not change significantly despite adequate antipsychotic treatment, and consequent improvements in psychopathology (Mitra et al, 2014b).…”
Section: Introductionmentioning
confidence: 99%